2009
DOI: 10.1104/pp.109.141374
|View full text |Cite
|
Sign up to set email alerts
|

Apple Sucrose Transporter SUT1 and Sorbitol Transporter SOT6 Interact with Cytochromeb5to Regulate Their Affinity for Substrate Sugars    

Abstract: Sugar transporters are central machineries to mediate cross-membrane transport of sugars into the cells, and sugar availability may serve as a signal to regulate the sugar transporters. However, the mechanisms of sugar transport regulation by signal sugar availability remain unclear in plant and animal cells. Here, we report that a sucrose transporter, MdSUT1, and a sorbitol transporter, MdSOT6, both localized to plasma membrane, were identified from apple (Malus domestica) fruit. Using a combination of the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 101 publications
(121 reference statements)
1
87
0
Order By: Relevance
“…Research presented here demonstrates that while AtSUC2p is repressed, CoYMVp is up-regulated in the presence of elevated Suc levels and thus can be used to bypass possible endogenous regulation of AtSUC2 expression at the transcriptional level. In addition to transcriptional regulation, there is evidence for posttranslational regulation of SUT activity through protein-protein interactions (Schulze et al, 2003;Krügel et al, 2008Krügel et al, , 2009Fan et al, 2009). To potentially bypass these levels of regulation, SUT genes from each of the four subfamily types (Reinders et al, 2012) were tested for the capacity to SUT OE lines perceive a P deficiency as indicated by rescue of wild-type (WT) levels of growth with P supplements and increased expression of PSI genes.…”
Section: Discussionmentioning
confidence: 99%
“…Research presented here demonstrates that while AtSUC2p is repressed, CoYMVp is up-regulated in the presence of elevated Suc levels and thus can be used to bypass possible endogenous regulation of AtSUC2 expression at the transcriptional level. In addition to transcriptional regulation, there is evidence for posttranslational regulation of SUT activity through protein-protein interactions (Schulze et al, 2003;Krügel et al, 2008Krügel et al, , 2009Fan et al, 2009). To potentially bypass these levels of regulation, SUT genes from each of the four subfamily types (Reinders et al, 2012) were tested for the capacity to SUT OE lines perceive a P deficiency as indicated by rescue of wild-type (WT) levels of growth with P supplements and increased expression of PSI genes.…”
Section: Discussionmentioning
confidence: 99%
“…Among the proteins that the literature reports to respond to general metabolism were found: a CR9 protein involved in plant growth and development by regulating cell cycle (Alfenas-Zerbini et al 2009), a succinate dehydrogenase related to mitochondrial respiration (Millar et al 2004) and cytochrome B5 implicated in sugar transportation interviewing with flowering and fruit development (Fan et al 2009).…”
Section: Number Of Sequencesmentioning
confidence: 99%
“…Recently, novel posttranslational regulation of Suc transporters was suggested from a study identifying interactions between cytochrome b 5 and Suc and sorbitol transporters (Fan et al, 2009). A split-ubiquitin system, coimmunoprecipitation, and bimolecular fluorescence were used to show that the apple (Malus domestica) Suc symporter MdSUT1 and the apple sorbitol transporter MdSOT6 both interact with the apple endoplasmic reticulum-localized cytochrome b 5 protein encoded by MdCYB5.…”
Section: Regulation Of Phloem Loadingmentioning
confidence: 99%